Investigation of the Structural, Thermal, Spectroscopic, and Electronic Properties of Praseodymium-based Hydroxyapatites Co-doped with Silver and Zinc in Varying Concentrations - Kareem, Rebaz Obaid; Ates, Tankut; Barzinjy, Azeez A.; Temuz, Mehmet Mursit; Ince, Turan; Bulut, Niyazi; Kaygili, Omer (Budapest Univ Technology Economics, 2025)
This study investigates the crystal structure, energy gap, band structure, spectroscopy, thermal, and electrical properties of Pr3+-based hydroxyapatites (HAp) co-doped with Zn2+ and Ag+ in varying concentrations. The synthesized samples, designated as 0.25Zn-0.25PrHAp, 0.50Zn-0.25Pr-HAp, 0.75Zn-0.25Pr-HAp, 0.25Ag-0.25Pr-HAp, 0.50Ag-0.25Pr-HAp, and 0.75Ag-0.25Pr-HAp, were prepared using a wet chemical method. The materials were characterized by Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), differential thermal analysis (DTA), and thermogravimetric analysis (TGA). Additionally, theoretical calculations employing density functional theory (DFT) were conducted to analyze the band structure (BS), energy gap (Eg; EHOM & oacute;ELUMO), and density of states (DOS). Results revealed a progressive reduction in the bandgap with increasing dopant concentrations, particularly in Ag-doped samples. Notably, 0.75Ag-0.25Pr-HAp exhibited the smallest bandgap of 3.983 eV, indicating enhanced electronic conductivity and potential applications in bioelectronics and medical sensors. Furthermore, the co-doped samples demonstrated reduced crystallinity, larger crystallite sizes, and excellent stability in biological environments, alongside superior biocompatibility and antibacterial properties. Among the synthesized materials, 0.75Ag-0.25Pr-HAp exhibited promising characteristics as a biomedical material for bone-related applications, owing to its structural stability, enhanced electrical properties, and suitability in antibacterial and bioelectronic devices. This investigation highlights the versatility of Zn/Ag co-doped Pr-HAp materials for advanced biomedical and technological applications.
Keywords: hydroxyapatite; Zn/Ag co-doping; praseodymium-based hydroxyapatites; bandgap; wet chemical method